The degree of damage to the gastroduodenal zone in patients with rheumatoid arthritis against the background of basic and anti-inflammatory therapy (Texas Journal of Medical Science, 2023)
To study the incidence of gastroduodenal lesions and the frequency of drug use in patients with rheumatoid arthritis based on retrospective analysis